2021
DOI: 10.1371/journal.pone.0256864
|View full text |Cite
|
Sign up to set email alerts
|

Peptide vaccines designed with the aid of immunoinformatic against Caseous Lymphadenitis promotes humoral and cellular response induction in mice

Abstract: Caseous Lymphadenitis (CLA) is a chronic disease that affects also small ruminants. CLA is caused by Corynebacterium pseudotuberculosis and is responsible for high economic losses due to the formation of superficial and visceral granulomas, the latter is considered as asymptomatic CLA causing high levels of dissemination. Several vaccination strategies, in which the use of synthetic peptides stands out. Thus, this work aimed to evaluate the protective potential of peptide vaccines designed to determine the imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Previous studies have already shown that IgG2a levels associated with the Th1 response highly correlate with phagocytic capacity [ 26 ]. Several studies using recombinant C. pseudotuberculosis proteins to compose vaccine formulations also reported significant levels of IgG2a production leading to the Th1-type immune response and generating protection in challenged animals [ 9 , 24 , 29 ], corroborating the results found here. Finally, even though the G2 and G3 groups had the same number of animals protected against the challenge when comparing IgG levels, the G2 group elicited the highest levels of antibodies, and that can be attributed to the use of the saponin adjuvant.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies have already shown that IgG2a levels associated with the Th1 response highly correlate with phagocytic capacity [ 26 ]. Several studies using recombinant C. pseudotuberculosis proteins to compose vaccine formulations also reported significant levels of IgG2a production leading to the Th1-type immune response and generating protection in challenged animals [ 9 , 24 , 29 ], corroborating the results found here. Finally, even though the G2 and G3 groups had the same number of animals protected against the challenge when comparing IgG levels, the G2 group elicited the highest levels of antibodies, and that can be attributed to the use of the saponin adjuvant.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, several studies have already used the saponin adjuvant associated with C. pseudotuberculosis antigens. The study by Droppa-Almeida et al (2021) showed that the saponin adjuvant was associated with peptides from the CP40 protein of C. pseudotuberculosis [ 24 ]. Moreover, in the studies by Droppa-Almeida et al (2016) and Silva et al (2014), vaccines for CLA containing recombinant antigens associated with saponin protected 90% and 100% of immunized animals, respectively [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although all groups were affected during the challenge with a virulence strain, they also showed the production of total IgG antibodies and cytokines (IL-2, IL-4, IL-6, IFN-γ, and TNF-α), indicating a possible activation of the Th1 type response. The authors suggest the use of adjuvants based on PAMPs to improve the immune response offered by these peptides [ 32 ]. Since peptide sequences are also included on some predicted epitopes in our work, we consider it interesting to evaluate a multi-epitope vaccine with the combination of all peptides in the same formulation to enhance levels of protection.…”
Section: Discussionmentioning
confidence: 99%
“…Splenocytes were harvested and distributed into 96-well plates as described previously [ 24 ]. CD4+T cells were isolated using immunomagnetic beads (MACS beads, USA) and examined by the flow cytometry for purity.…”
Section: Methodsmentioning
confidence: 99%